PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK MENGGUNAKAN MEDIA REALIA PADA PEMBELAJARAN IPA DI SD - Lia Nurhayati; Salatifah Salatifah (LPPM Universitas Muhammadiyah Gorontalo, 2021)
The purpose of this research was to increase the learning motivation of students in science learning through the use of Reality learning media. With the formulation of the problem whether educators using reality media in science learning theme 6 Heat and Transfer material in class V SD Negeri 18 Pulubala, Gorontalo Regency can increase students' learning motivation. The subjects of this classroom action research were students of class V SD Negeri 18 Pulubala with a total of 18 people and the main target in this research was to increase the learning motivation of students in science learning theme 6 Heat and its displacement. The performance indicators used are learning activities that are said to be complete if the active and very active categories classically reach more than 80%. The results of this research indicate an increase in the learning motivation of students in the first cycle stage of the active and very active category on average reaching 69,14%. The results of cycle II have started to reach indicators of success. This is indicated by the average acquisition it reached 83%. The results of the competency test in cycle II are better than cycle I. This shows that the activities of students during learning have been very active, so that they have increased learning motivation.Tujuan penelitian ini adalah untuk meningkatkan motivasi belajar peserta didik pada pembelajaran IPA melalui penggunaan media pembelajaran Realita. Dengan rumusan masalah apakah pendidik dengan menggunakan media realita pada pembelajaran IPA tema 6 materi Panas dan Perpindahannya di kelas V SD Negeri 18 Pulubala Kabupaten Gorontalo dapat meningkatkan motivasi belajar peserta didik. Subyek Penelitian tindakan kelas ini adalah peserta didik kelas V SD Negeri 18 Pulubala dengan jumlah 18 orang dan sasaran utama dalam penelitian ini adalah meningkatkan motivasi belajar peserta didik pada pembelajaran IPA tema 6 materi Panas dan perpindahannya. Indikator kinerja yang digunakan adalah kegiatan pembelajaran dikatakan tuntas apabila kategori aktif dan sangat aktif secara klasikal mencapai lebih dari 80 %. Hasil penelitian ini menunjukkan adanya peningkatan motivasi belajar peserta didik pada tahap siklus I mencapai rata-rata 69,14%, Hasil pencapain siklus II sudah mulai mencapai indikator keberhasilan. Hal ini ditunjukkan dengan perolehan rata-rata siklus II mencapai 83%. Hasil uji kompetensi siklus II lebih baik dari siklus I. Hal ini nampak kegiatan peserta didik selama pembelajaran sudah sangat aktif, sehingga mengalami peningkatan motivasi belajar.